2020
DOI: 10.1111/tbed.13793
|View full text |Cite
|
Sign up to set email alerts
|

First report of the infectious spleen and kidney necrosis virus (ISKNV) infection in ornamental fishes in India

Abstract: Infectious spleen and kidney necrosis virus (ISKNV), a member of family iridoviridae, reported for the first time in a wide range of ornamental fish species in India.Significant mortalities during the year 2018-19 were reported from a number of retailers in the region with various clinical signs. The samples of moribund, dead and apparently healthy ornamental fishes were collected from retailers, located in three districts of Karnataka, India. Out of 140 fish samples, 16 samples (11.42%) repre-How to cite this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…To the best of our knowledge, this is the first time that a disease outbreak in giant gourami due to ISKNV infection has been reported in India. However, previous reports of ISKNV from India were from asymptomatic apparently healthy fishes (Girisha, Kushala, et al, 2020;Pattanayak et al, 2020). Furthermore, the similarity of the MCP gene fragment recovered from infected fish in our study to that of other iridovirus strains reported from various countries suggests the origins of this outbreak might have some common channels in the ornamental fish trade.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first time that a disease outbreak in giant gourami due to ISKNV infection has been reported in India. However, previous reports of ISKNV from India were from asymptomatic apparently healthy fishes (Girisha, Kushala, et al, 2020;Pattanayak et al, 2020). Furthermore, the similarity of the MCP gene fragment recovered from infected fish in our study to that of other iridovirus strains reported from various countries suggests the origins of this outbreak might have some common channels in the ornamental fish trade.…”
Section: Discussionsupporting
confidence: 49%
“…The major viral diseases identified in giant gourami include tilapia lake virus (TiLV) (Jaemwimol et al, 2018) and giant gourami iridovirus (GGIV): a new infectious spleen and kidney necrosis virus (ISKNV) (Sukenda et al, 2020). In India, ISKNV was reported from healthy asymptomatic ornamental fish (Girisha, Kushala, et al, 2020;Pattanayak et al, 2020) during routine aquatic animal disease surveillance. But in our study, we investigated a disease outbreak in giant gourami farms in Kerala, India, through viral isolation followed by clinical, histopathological, and genetic analyses and bioassays thereby confirmed the causative agent as ISKNV.…”
mentioning
confidence: 99%
“…Since red seabream iridovirus (RSIV) was firstly documented in cultured red seabream in Shikoku Island, Japan, in 1990 [ 25 ], and the genus Megalocytivirus was defined in 2005 [ 26 ]; in the past 30 years, megalocytivirus has become a worldwide threat to extensive farmed freshwater and marine bony fish distribution in Asia, Europe, America, Africa, and Australia [ 3 , 5 , 27 , 28 ]. The traditional megalocytiviruses were composed of three classic clades, namely RSIV, ISKNV, and TRBIV, and a further six subclades of RSIV-I and RSIV-II, ISKNV-I and ISKNV-II, and TRBIV-I and TRBIV-II.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, megalocytiviruses have attracted great interest as they cause lethal systemic infections in wild and cultured freshwater, brackish, and marine bony fish worldwide [ 3 , 4 ]. Based on the nucleotide sequences of the viral major capsid protein ( mcp ) and adenosine triphosphatase ( ATPase ) genes, traditional megalocytivirus could be divided into three genotypes, and each genotype could be further subdivided into two separate subclades [ 5 ]: red sea bream iridovirus (RSIV), which has been reported in Japan, Korea, mainland China, Chinese Taiwan, and Southeast Asia, has caused serious economic loss in red seabream Pagrus major and many other marine and freshwater fish species [ 4 , 6 ]; infectious spleen and kidney necrosis virus (ISKNV), which has caused high mortality in mandarin fish Siniperca chuatsi in mainland China, has been reported as a major viral causative agent in tilapia Oreochromis niloticus , zebrafish Danio rerio , bluegill sunfish Lepomis macrochirus , and a variety of ornamental fishes [ 3 , 7 , 8 , 9 ]; and turbot reddish body iridovirus (TRBIV) mainly affects flatfish [ 5 ]. Complete genomic sequences of several ISKNV, RSIV, and TRBIV isolates have been determined and annotated, and the virion-associated proteins of both ISKNV-type and RSIV-type megalocytiviruses were identified by comprehensive proteomic approaches [ 5 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A major cause of mortality of wild and aquaculture fish stocks worldwide is the result of introduced pathogens, primarily due to anthropogenic translocations [ 1 , 2 , 3 ]. Indeed, the widespread and high-volume trade of common carp ( Cyprinus carpio , carp), and their ornamental variety, koi, has been associated with the transportation of viral pathogens worldwide with introductions to naïve captive and wild populations [ 4 , 5 , 6 ]. Not native to the continent, common carp have been introduced throughout North America for over a century.…”
Section: Introductionmentioning
confidence: 99%